Testes reais de recomposição: proposta aplicada a projetos de usinas hidrelétricas de autorrestabelecimento - Jenaina Aparecida de Souza (2014)
This thesis addresses the Real Tests for Hydroelectric Plants Restoring Process. The work proposes a new innovative proceeding, by the use of guidelines, applied to hydroelectric project area. The proceeding aims the elaboration of adequate plants project in order to prepare them for future test conditions required during real time operation. It is proposed a computational tool, called SIAPE Disturbance Automatic Simulator, in order to consolidate the entire strategy.